The measurement of multiple influence paths of residents' positive perception in ethnic minority village tourism destinations: a case study of Ping'an Zhuang Village in Longsheng County - Wei, Yin; Lin, Ling (Frontiers in Sustainable Tourism, 2025)
Ethnic tourism is a delightful activity for tourists to visit ethnic minority gathering areas to fulfill their aesthetic demands by observing and experiencing the cultures of ethnic minorities. Based on the grounded theory, quantitative analysis and fuzzy set qualitative comparative analysis, this paper delves into the measurement of the positive perception of residents in ethnic minority villages and the multiple paths of its influencing factors, aiming to offer policy notions for promoting the dynamic protection of ethnic minority culture and rural revitalization. The findings revealed that: (1) The positive perception of residents in tourist destinations can be classified into three dimensions: “positive perception in economy,” “positive perception in social and cultural aspects,” and “positive perception in environment,” and the localized scale encompasses nine items; (2) The influencing factors consist of three elements: place belonging, perceived power, and residents' participation. The enhancement of residents' positive perception demands a combination of these factors rather than relying solely on any single one; (3) Regarding the perception of residents in any dimension, the direct impact of perceived power on the positive perception of residents in ethnic villages is weak. Place belonging and residents' participation are the core conditions for the formation of the positive perception of residents in ethnic villages. Strengthening the emotional connection and participation mechanism of residents is an effective means to boost their positive perception.